Virtual application of in situ simulation during a pandemic. Issue 5 (September 2020) - Hanel, Erich; Bilic, Monika; Hassall, Kelly; Hastings, Mary; Jazuli, Farah; Ha, Michael; Trotter, Brendon; Fraser, Cory; Rutledge, Greg
ABSTRACT: The coronavirus disease 2019 (COVID-19) pandemic introduced challenges to the use of simulation, including limited personal protective equipment and restricted time and personnel. Our use of video for in situ simulation aimed to circumvent these challenges and assist in the development of a protocol for protected intubation and simultaneously educate emergency department (ED) staff. We video-recorded a COVID-19 respiratory failure in situ simulation event, which was shared by a facilitator both virtually and in the ED. The facilitator led discussions and debriefs. We followed this with in situ run-throughs in which staff walked through the steps of the simulation in the ED, handling medications and equipment and becoming comfortable with use of isolation rooms. This application of in situ simulation allowed one simulation event to reach a wide audience, while allowing participants to respect social distancing, and resulted in the education of this audience and successful crowdsourcing for a protocol amidst a pandemic.